Membangun Budaya Organisasi dalam Pendidikan Islam di Pesantren - Susilowatik, Susilowatik; Syarif, Zainuddin; Qasim, Ahmad (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2024)
Organizational culture is very crucial in its existence within the organization, because it affects the emergence of good behavior and improves performance, both from leaders and members and determines the direction of the organization in the long and short term. An established organizational culture will create an atmosphere of cooperation, cooperation, and not pranking others. This study uses a qualitative approach. That is, this study seeks to analyze, record, describe, and interpret the object under study through observation, interviews, and reviewing documentation. This research is also descriptive of the data extracted through the field and literature. The findings show that building an organizational culture at the Mambaul Ulum Bata-Bata Islamic boarding school (girls) refers to traditional and modern approaches, which in turn emerges a culture of good behavior and a culture of commitment to the organization such as discipline, sincerity, trustworthiness, openness, and democracy.